Examination of Effect of Electrochemically Activated Water Solutions on Candida albicans After Different Periods of Storage - Popova, Prof. Teodora P. (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
Studies to determine the sensitivity of Candida albicans to anolyte and catholyte of 0.5% NaCl and a combination of 0.5% NaCl and 0.5% Na2CO3 were performed. Both anolytes killed the tested strains in suspensions (106 cells/ml) within 5 min. The catholytes showed low antimicrobial activity. The inhibitory properties of the tested anolytes were fully preserved over a period of 2 months when stored in the dark at room temperature, but of the catholytes - for no more than 2 weeks. These results show that anolytes are promising antimicrobial agents with very high activity against C. albicans.